Personal Qualities of an Entrepreneur: 5C model in Entrepreneur’s Success - Ms. A.Sahanas Banu, Dr.A.R.Nithya, Dr.P.Kannadas (International Journal of Advanced Science and Technology, 2020)
The objective of the present study is to analyse the factors influencing the entrepreneurship and the impact of the moderating variables in the entrepreneurship